Managing droughts in the low-rainfall areas of the Middle East and North Africa - Hazell, Peter B. R.; Oram, Peter; Chaherli, Nabil (International Food Policy Research Institute, 2001)
Drought is a recurrent and often devastating threat to the welfare of countries in the Middle East and North Africa (MENA) where three-quarters of the arable land has less than 400 mm of annual rainfall, and the natural grazings, which support a majority of the 290 million ruminant livestock, have less than 200 mm. Its impact has been exacerbated in the last half century by the human population increasing yearly at over 3%, while livestock numbers have risen by 50% over the quinquennium. Virtually no scope exists for further expansion of rainfed farming and very little for irrigation, hence there is competition between mechanized cereal production and grazing in the low rainfall areas, and traditional nomadic systems of drought management through mobility are becoming difficult to maintain. Moreover droughts seem to be increasing in frequency, and their high social, economic, and environmental costs have led governments to intervene with various forms of assistance to farmers and herders, including distribution of subsidized animal feed, rescheduling of loans, investments in water development, and in animal health. In this paper we examine the nature and significance of these measures, both with respect to their immediate benefits and costs to the recipients and to governments, and to their longer term impact on poverty and the environment. We conclude that while they have been valuable in reducing catastrophic losses of livestock and thus alleviating poverty, especially in the low rainfall areas where they are the predominant source of income, continued dependence on these programs has sent inappropriate signals to farmers and herders, leading to moral hazards, unsustainable farming practices, and environmental degradation, while generally benefiting the affluent recipients most.